In Adult Skeletal Muscles, the Co-Receptors of Canonical Wnt Signaling, Lrp5 and Lrp6, Determine the Distribution and Size of Fiber Types, and Structure and Function of Neuromuscular Junctions - Lea Gessler; Christopher Kurtek; Mira Merholz; Yongzhi Jian; Said Hashemolhosseini (Cells, 2022)
Canonical Wnt signaling is involved in skeletal muscle cell biology. The exact way in which this pathway exerts its contribution to myogenesis or neuromuscular junctions (NMJ) is a matter of debate. Next to the common co-receptors of canonical Wnt signaling, Lrp5 and Lrp6, the receptor tyrosine kinase MuSK was reported to bind at NMJs WNT glycoproteins by its extracellular cysteine-rich domain. Previously, we reported canonical Wnt signaling being active in fast muscle fiber types. Here, we used conditional Lrp5 or Lrp6 knockout mice to investigate the role of these receptors in muscle cells. Conditional double knockout mice died around E13 likely due to ectopic expression of the Cre recombinase. Phenotypes of single conditional knockout mice point to a very divergent role for the two receptors. First, muscle fiber type distribution and size were changed. Second, canonical Wnt signaling reporter mice suggested less signaling activity in the absence of Lrps. Third, expression of several myogenic marker genes was changed. Fourth, NMJs were of fragmented phenotype. Fifth, recordings revealed impaired neuromuscular transmission. In sum, our data show fundamental differences in absence of each of the Lrp co-receptors and suggest a differentiated view of canonical Wnt signaling pathway involvement in adult skeletal muscle cells.